Fortification and bioaccessibility of saffron apocarotenoids in potato tubers - Gómez Gómez, Lourdes; Morote, Lucía; Frusciante, Sarah; Rambla, José Luis; Diretto, Gianfranco; Niza, Enrique; López-Jimenez, Alberto José; Mondejar, María; Rubio-Moraga, Ángela; Argandoña, Javier; Presa, Silvia; Martín-Belmonte, Alejandro; et al. (Frontiers in Nutrition, 2022)
Carotenoids are C40 isoprenoids with well‐described functions in photosynthesis, pollination, photoprotection and hormone biosynthesis. The enzymatic or ROS-induced cleavage of carotenoids generate a group of compounds named apocarotenoids, with an increasing interest by virtue of their metabolic, physiological and ecological activities. Industrially, both classes are used across multiple commercial sectors as colorants, supplements, and bio-actives. Apocarotenoids comprise a variety of molecules derived from the enzymatic cleavage of carotenoids. Some saffron apocarotenoids (crocins and picrocrocin) are examples of high value pigments used in the food, feed, and health sectors. In this study, a unique construct named O6, containing CsCCD2L, UGT74AD1 and UGT709G1 genes responsible for the biosynthesis of saffron apocarotenoids under the control of a patatin promoter for the generation of potato tubers producing crocins and picrocrocin, was achieved. Different tuber potatoes accumulated crocins and picrocrocin ranging from 19.41-360ug/g and 105-800ug/g DW, respectively, being crocetin, crocin 1 [(crocetin-(B-D-glucosyl)-ester)] and crocin 2 [(crocetin)-(B-D-glucosyl)-(B-D-glucosyl)-ester)] the main compounds detected. The pattern of carotenoids and apocarotenoids were distinct between wild type and transgenic tubers and were related to changes in the expression of the pathway genes, especially from PSY2, CCD1 and CCD4. In addition, the engineered tubers showed higher antioxidant capacity, up to almost 4-fold more than the wild type, which represents a good indicator of the health benefits that might be derived from these lines. In order to better investigate these aspects, different cooking methods were applied, and each process displayed a significant impact on the retention of apocarotenoids. More in detail, the bioaccessibility of these metabolites was found to be higher in boiled potatoes (97.23%) compared to raw, baked, and fried ones (80.97%, 78.96% and 76.18%, respectively). Overall, his work shows that potatoes can be engineered to accumulate saffron apocarotenoids that, when consumed, can potentially offer better health benefits. Moreover, the high bioaccessibility of these compounds revealed that potato is an excellent system to deliver crocins and picrocrocin, and represents a promising strategy to improve the potato nutritional value.